164 Effects of Dabrafenib and Trametinib, Cancer Therapies that Target Braf and MEK, on Cardiac Signalling. (31st May 2014) - Clerk, Angela; Connell, Luke; Pipe, Michelle; Fuller, Stephen J; Sugden, Peter H
Abstract : Introduction: The extracellular signal-regulated kinase (ERK1/2) cascade is associated with cardioprotection and cardiac hypertrophy. However, constitutive ERK1/2 signalling is also associated with cancer. Inhibitors of BRaf (e.g., dabrafenib) and MEK (trametinib) are in clinical use as cancer therapies. The molecular effects of BRaf and MEK inhibitors on the heart remain to be established. Methods: Adult rat hearts were perfused in the Langendorff mode under control conditions, with dabrafenib or trametinib alone, with fibroblast growth factor (FGF) or with FGF in the presence of dabrafenib or trametinib. Signalling through the ERK1/2 cascade and potential off-target effects on the cytoprotective Akt pathway were assessed by immunoblotting. Results: Perfusion of rat hearts with dabrafenib significantly inhibited baseline phosphorylation (i.e. activation) of MEK and ERK1/2, whilst trametinib inhibited baseline activation of ERK1/2 but not MEK. These data suggest that BRaf activity is required for basal ERK1/2 activity in the heart. Both inhibitors prevented activation of ERK1/2 and downstream kinases (p90 RSK, p70 S6K) by FGF further indicating that peptide growth factor signalling is mediated by BRaf in the heart. Interestingly, trametinib enhanced Akt signalling in control and FGF-perfused hearts. Both inhibitors increased phosphorylation of c-Raf(Ser-338), one of the key activating phosphorylations, presumably because feedback inhibition from ERK1/2 was lost. Conclusions: BRaf and MEK inhibitors in use for cancer therapy suppress basal and growth factor induced activation of ERK1/2 signalling suggesting that they are likely to have cardiotoxic effects. However, potentially damaging inhibition of ERK1/2 signalling by TRAM may be mitigated in part by enhanced cytoprotection via Akt assuming this pathway is not compromised.